Evaluation of Total Phenolic, Flavonoid Content and Antioxidant Capacity of Different Parts of Averrhoa carambola L. (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Averrhoa carambola L. belonging to the Oxalidaceae family has fruits with attractive star shape. Total phenolic and flavonoid content and antioxidant capacity of various parts of A. carambola have been studied to explore active extracts for novel antioxidant compounds. Methanol extract of bark contained the highest amount of phenolic constituent (125 mg GAE/g of dry extract). However, hexane, dichloromethane and methanol extracts contained the maximum number of flavonoids and were 45, 92 and 72 mg QE/g of dry extract, respectively. Since the bark possessed the highest antioxidant capacity, it contained more phenolic compounds than other extracts of fruits and leaves. Total antioxidant capacity of hexane, dichloromethane and methanol extracts of bark were 62, 117 and 151 mg AAE/g of dry extract, respectively. The results recommend that the bark part can be a good source of phenolic compounds as it showed the highest antioxidant capacity. The fruit and leave parts are also rich sources of antioxidant compounds.Dhaka Univ. J. Pharm. Sci. 21(2): 147-151, 2022 (December)